SUCCESSFUL MANAGEMENT OF POLYARTHRITIS WITH LINCOMYCIN IN A CALF-A CASE REPORT - Das, B C; Prasad, A Arun; Raj, H Pushkin; William, B Justin; Kumar, R Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Septic or polyarthritis is the most common clinical condition that affects the joints in cattle. Incidence of lameness related to joint diseases in cattle is well documented. Infectious arthritis may result from localization of bacteria, viral, mycotic or mycoplasma in a joint. With the presence of pus in the joint cavity, the infectious arthritis is termed as septic, pyogenic or suppurative arthritis. Haematogenous origin of infectious arthritis is the most common disease encountered in young calves as joint ill or neonatal polyarthritis. Staphylococcus aureus, Streptococci spp., Corynebacterium pyogenes, E. coli, and Salmonella spp. are the most frequently implicated organisms for causing infectious arthritis in cattle. The presence of fibrin deposits over the synovial membrane and articular cartilage decreases the nutritive effectiveness of synovial fluid and inhibits the diffusion of antibiotics used to treat septic arthritis (Bertone, 1996). Lincomycin is an antibacterial agent widely used to treat gram-positive aerobic and anaerobic infections that are resistant to the β-lactamase antibiotics (Spoo and Riviere, 1995). The successful treatment of arthritis and pedal osteomyelitis with lincomycin was reported by Pleviderleith (1988).